Differential effects of type 2 diabetes and gestational diabetes on maternal and cord blood adipokines and newborn weight - Brittany L. Gruber; Yash Rawal; Priscilla Irabor; Elizabeth A. C. Sellers; Christy Pylypjuk; Vernon W. Dolinsky; Brandy A. Wicklow (BMC Pregnancy and Childbirth, 2025)
Abstract Background Dysregulated adipokine levels are associated with type 2 diabetes and gestational diabetes. Adiponectin and leptin are involved in nutrient transport, thereby affecting fetal growth and metabolism. We aimed to determine whether type 2 diabetes and gestational diabetes were associated different levels of serum and cord blood adiponectin, leptin, insulin and offspring birthweight. Methods Serum, cord blood, gestational age and birthweight were collected for First Nations mothers and infants who were enrolled in the Next Generation Cohort Study. A total of 173 maternal and 188 neonatal samples were available for analysis. Of those, 136 were matched maternal infant dyads that we used for paired mother-infant analyses. Pairs were sorted into groups based on maternal diagnoses of pre-existing type 2 diabetes, gestational diabetes or no diabetes (control). Adiponectin and leptin were measured by enzyme linked immunosorbent assay. Results Mothers with gestational diabetes had lower serum adiponectin (6.48 ± 3.64 µg/mL) in the third trimester relative to mothers with type 2 diabetes (8.55 ± 5.24 µg/mL, p < 0.05) or no diabetes (7.73 ± 3.47 µg/mL). However, cord blood adiponectin was lower only in normal weight pregnancies complicated by type 2 diabetes. Cord blood glucose, insulin and leptin were increased in infants of type 2 diabetes mothers and increased leptin was positively correlated with maternal leptin and birth weight. Female infants exposed to pregestational type 2 diabetes had a significantly higher birthweight z-score than female control infants. Conclusions In this study, exposure to type 2 diabetes, but not gestational diabetes, impacted cord blood levels of glucose, insulin and leptin and birthweight. Collectively, these factors may contribute to the greater impact of pregestational type 2 diabetes exposure on offspring health relative to gestational diabetes.